Some Thoughts on Official Statistic and its Future - Tillé, Yves (My University, 2021)
In this article, we share some reflections on the state of statistical science and its evolution in the production systems of official statistics. Data sources and methods are evolving, raising questions about the future of official statistics. The history of the methods used deserves a closer look at the changes that are taking place in the world of official statistics.
Keywords: deduction; induction; Lasso; p-value; register; sampling; statistical learning